Internationalisation of African higher education : towards achieving the MDGs - Sehoole, Chika; Knight, Jane (Global perspectives on higher education, 2013)
The role of higher education, especially the international dimension, is given little importance in the discourse on achieving the Millennium Development Goals (MDGs) in Africa. This book aims to change that. The potential of higher education’s contribution to Africa’s development remains unrealized and often misunderstood. In today’s globalised world, which prioritises economic growth through liberalised trade and competitive market strategies, much emphasis has been placed on higher education’s ability to produce graduates to serve the labour market and produce new knowledge for the knowledge economy. While these are important contributions, the book argues that international higher education and new knowledge must go beyond economic purposes and serve the human and social development needs of the continent. It is against this background that the African Network for the Internationalisation of Education (ANIE) undertook research on the international dimension of higher education in Africa and its role in the achievement of the MDGs. Through empirical research, seven case studies address how international and regional higher education programmes and policies in African universities can address MDG priorities of promoting gender equality and women’s empowerment, combating HIV/AIDS and establishing global partnerships for development through academic mobility, joint research initiatives, curriculum innovation and policy development.
Keywords: Education, Higher : Africa; Globalization : Africa; Education and globalization : Africa